Morphological study of nitrides of NbTi (50:50, by weight) alloy - Teixeira, Silvio Rainho [UNESP]; de Anchieta Rodrigues, Jose; Mascarenhas, Yvonne Primerano (Elsevier B.V., 1993)
Plates of NbTi (50:50, by weight) were nitrided in a nitrogen atmosphere in the temperature range 800-1000 °C for 15, 30, 60, 120 and 180 min. X-Ray diffraction and optical and electronic microscopy were used to characterize the samples. Two nitride layers were identified on the substrate: an external and continuous phase of TiN, named δ, and a deeper and discontinuous phase of Ti 2N, named ε{lunate}. The electron micrographs reveal the presence of paths rich in Nb which may be responsible for the diffusion of nitrogen into the matrix. © 1993.